2009
DOI: 10.1002/jbm.b.31302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrasound evaluation of human trabecular bone graft properties after treatment with different sterilization procedures

Abstract: New sterilization methods for human bone are likely to affect the mechanical properties of human cancellous grafts. These mechanical properties dictate the short- and mid-term results of the orthopedic procedure. The aim of this study was to compare the effects on bone mechanical properties, as assessed by ultrasound velocity, of different sterilization methods used under similar conditions: bleach and sublimation, humid heat, successive baths of physiological saline with osmotic detersion, and CO(2) in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
6
2
2
Order By: Relevance
“…Preclinical studies have shown that this process used on bone has neutral effects on the bone tissue composition; preserves its architecture and mechanical properties, particularly its high wettability, and thus improves performance [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that this process used on bone has neutral effects on the bone tissue composition; preserves its architecture and mechanical properties, particularly its high wettability, and thus improves performance [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Our technique has several advantages ( Table 2 ): The existing tibial tunnel is filled completely with allograft bone, whose mechanical properties and architecture are identical to those of fresh bone. 23 , 24 , 25 This allows us to drill a new tibial tunnel without having to worry about overlap. Since the existing tibial tunnel is filled, the revision can be carried out like a primary ACL reconstruction procedure, with no need to worry about the previous tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Необходимость очистки кости от органиче-ских компонентов обусловлена двумя аспек-тами: снижением риска передачи инфекции и снижением антигенного и воспалительного потенциала [28]. по мнению R. Lomas с соавто-рами, очистка повышает клиническую эффек-тивность и безопасность материалов [3].…”
Section: очистка и первичная дезинфекцияunclassified